THE CURRENT STATE AND DEVELOPMENT PROSPECTS OF THE AGRO-INDUSTRIAL COMPLEX OF THE REPUBLIC OF KAZAKHSTAN - Kazhieva Zhania Khaidarovna; Zhailaubayeva Shynar Dalelovna; Zeinullina Aigul Zhumagalievna; Parimbekova Lyazzat Zaithanovna (Academic Journal of Physical and Chemical Sciences, 2020)
The development of agribusiness in Kazakhstan is a promising task and is associated with the creation of technological systems for storage and processing of agricultural raw materials in the production of environmentally friendly, competitive food products of general and special purpose based on modern achievements of nano-, biotechnology. The solution to the problems of the development of the agro-industrial complex is determined by the level of financing, mainly from the state budget, which should be carried out on the basis of the principles of strategic planning, on the basis of concentration on the essential and priority directions of increasing the competitiveness of agriculture and ensuring food security.